Na boca do inferno: A América diabólica projetada pela Companhia de Jesus - Cressoni, Fábio Eduardo [UNESP] (Universidade Estadual de Maringa, 2014)
Current paper investigates the symbolic representations built by Jesuit missionaries on the supposed presence of the devil in 16th century Portuguese America. The items that foregrounded the construction of a specific infernal site are indicated through the analysis of a series of documents produced by the Jesuits, which typified the Tupinambá characteristics. Throughout the process, the transference of such harmful influence occurred towards the specific being of this social group, namely the Caraíba, the character identified by the Society of Jesus as the main enemy of the catechetical activities of the order of Ignatius of Loyola.
In the mouth of hell: Bedeviled America projected by the Society of Jesus
Keywords: Demonization; Society of Jesus; Tupinambá